Assessment of the RNASound RNA Sampling Card for the Preservation of Influenza Virus RNA - Lau, Hilda; Hurt, Aeron C. (Frontiers in Microbiology, 2016)
Shipping influenza virus specimens, isolates or purified RNA is normally conducted at ultra-low temperatures using dry ice to ensure minimal degradation of the samples but this is expensive and requires special packaging and shipping conditions. Therefore, alternative methods for shipping influenza viruses or RNA at ambient temperatures would be desirable. The RNASound RNA Sampling Card (FortiusBio LLC, CA, USA) is a device that enables specimens or isolates to be applied to a card, whereby viruses are inactivated, while RNA is preserved and purified RNA can also easily be eluted. To evaluate this card, we applied influenza virus cell culture isolate supernatants to either the RNASound card or Whatman Grade No. 1 filter paper (GE Healthcare, NSW, Australia) and compared the preservation to that of material stored in liquid form. Preservation was tested using influenza A and B viruses at two different storage temperatures (cool [2-8oC] or room temperature [18-22oC]) and these were compared with control material stored at -80°C, for 7, 14 or 28 days. The quality of the RNA recovered was assessed using real time RT-PCR and Sanger sequencing. The RNASound card was effective in preserving influenza RNA at room temperature for up to 28 days, with only a minor change in real-time RT-PCR cycle threshold values for selected gene targets when comparing between viruses applied to the card or stored at -80°C. Similar results were obtained with filter paper, whilst virus in liquid form performed the worst. Nevertheless, as the RNASound card also has the capability to inactivate viruses in addition to preserving RNA at room temperature for many weeks, this makes it feasible to send samples to laboratories using regular mail, and thus avoid the need for expensive shipping conditions requiring biohazard containers and dry ice. Moreover, the quick and simple RNA recovery from the RNASound card allows recipient labs to obtain RNA without the need for special reagents or equipment.